Les lémuriens subfossiles dans le Nord-Ouest de Madagascar, du terrain à la diffusion des connaissances ou 15 ans de recherches franco-malgaches - Dominique Gommery; Beby Ramanivosoa (Revue de Primatologie)
Madagascar is one of the most important hotspot of the world biodiversity. Among the numerous endemic animals living in the island, the lemurs are the more emblematic. Within the primate order, this group is one of the most diversified. If their origin is still not clear, numerous extinct subfossils species have been recorded for at least 26 000 years, the more recent ones being only a few hundred years old. The lemurs are mentioned in ancient texts or legends because of their size which made an impression on people. The causes of their extinction remain poorly known. Historically, the majority of the subfossil sites were known in two geographical areas: the South-West and the Center of Madagascar, which shared a few species. More recently, some subfossils have been discovered in the North of the island, but almost nothing was known in the North-West of Madagascar until 1997 when explorations were undertaken in the framework of a collaboration between malagasy and french researchers.Currently, 19 sites are known and many subfossils were discovered. A new species of extinct lemur was described, Palaeopropithecus kelyus. Numerous non-lemur taxa are recorded (micro-and macrofauna) and contribute to understand the history of the past biodiversity and palaeoenvironments.This fair collaboration is also a human adventure. The different participants of the two countries take an equal part in the fieldwork, the studies, the technical and academic training of the students at the University of Mahajanga, and the popularization of the results. Through exhibitions the new Malagasy generations are sensitized to the preservation of their geological and natural heritage.